Teachers’ ideas about children’s participation within Portuguese early childhood education settings - Correia, N. (2020)
This study investigated teachers’ ideas about children's right to participate in ECE. Participants were 59 teachers, aged between 26 and 60 years old (M = 43.07 years, SD = 8.58), all female, from 59 ECE classrooms from 24 randomly selected ECE centres located in the metropolitan area of Lisbon. Teacher's ideas were collected using a qualitative interview specifically designed for the purpose. Based on content analysis, multiple correspondence analysis, and cluster analysis, we identified profiles of teachers’ ideas and clusters of teachers. Results suggest four teacher profiles: Teachers motivation, Teachers’ conditioned responsibility, Children's benefits, and Context dependent. Profiles were significantly associated with years of professional experience and type of institution. Teachers’ age was significantly different across profiles. Findings provide insights to fuller understand teachers’ positioning about this right.